2004
DOI: 10.1673/031.004.2601
|View full text |Cite
|
Sign up to set email alerts
|

Protein-enriched pea flour extract protects stored milled rice against the rice weevil, Sitophilus oryzae

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
(12 reference statements)
0
5
0
Order By: Relevance
“…Tephrosia vogelii is reportedly as repellent to insects as the neem plant (Boeke et al 2004). This might have contributed to fewer females being attracted to grains treated with the hexane extract, thus resulting in the observed drastic reduction in the number of eggs deposited, as suggested for the rice weevil S. oryzae exposed to protein-enriched pea flour-treated rice (Fields et al 2001;Pretheep-Kumar et al 2004). The two other extracts obtained using the more polar solvents, acetone and ethanol, were ineffective.…”
Section: Discussionmentioning
confidence: 91%
“…Tephrosia vogelii is reportedly as repellent to insects as the neem plant (Boeke et al 2004). This might have contributed to fewer females being attracted to grains treated with the hexane extract, thus resulting in the observed drastic reduction in the number of eggs deposited, as suggested for the rice weevil S. oryzae exposed to protein-enriched pea flour-treated rice (Fields et al 2001;Pretheep-Kumar et al 2004). The two other extracts obtained using the more polar solvents, acetone and ethanol, were ineffective.…”
Section: Discussionmentioning
confidence: 91%
“…Acetone seed extract of Aphanamixis polystachya showed 100% repellent effects on red flour beetles [32]. Pretheep-Kumar et al [33] found a maximum of 91.2% of repellency with an extract of protein enriched bean flour on weevils, S. oryzae, after 48 h of the test period. e high insect repellent results seen in this study are also supported by Boateng and Kusi [34] who showed that J. curcas seed extracts could repel up to 95% of the C. maculatus and D. basalis.…”
Section: Discussionmentioning
confidence: 99%
“…Acetone seed extract of Aphanamixis polystachya showed 100% repellent effects on red flour beetles [ 32 ]. Pretheep-Kumar et al [ 33 ] found a maximum of 91.2% of repellency with an extract of protein enriched bean flour on weevils, S. oryzae , after 48 h of the test period.…”
Section: Discussionmentioning
confidence: 99%
“…Agron., 14 (4): 298-303, 2015 have reported that legume seeds contain a wide range of allelochemicals with toxic and deterrent effects against insect pests. The insecticide effect of pea flour on rice weevil (Sitophilus oryzae L.) have received the most attention (Hou and Fields, 2003;Pretheep-Kumar et al, 2004;Fields, 2006). Pea protein is repellent to several stored-product insects (Fields et al, 2001;Kumar et al, 2004) and toxic (Pretheep-Kumar et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The insecticide effect of pea flour on rice weevil (Sitophilus oryzae L.) have received the most attention (Hou and Fields, 2003;Pretheep-Kumar et al, 2004;Fields, 2006). Pea protein is repellent to several stored-product insects (Fields et al, 2001;Kumar et al, 2004) and toxic (Pretheep-Kumar et al, 2004). This toxicity is primarily correlated with the biological activity of a major albumin isolated from pea grains, pea albumin1 subunit b (PA1b) (Gressent et al, 2003).…”
Section: Introductionmentioning
confidence: 99%